Shear-bond strength and optical properties of short fiber-reinforced CAD/CAM composite blocks - Mangoush Enas; Lassila Lippo; Vallittu Pekka; Garoushi Sufyan (United States, 2022)
The aim of this study was to assess the shear-bond strength (SBS) of resin-luting cement to experimental short fiber-reinforced CAD/CAM composite (SFRC) compared to conventional CAD/CAM (Cerasmart 270), 3D printed (GC TEMP PRINT, Pro3dure GR-17), and laboratory (Gradia Plus) composites. Moreover, translucency parameter values and light transmission were evaluated. For each of the five types of composites, discs were prepared (n = 16/group) and divided into subgroups (n = 8/group) according to surface treatment protocol (hydrofluoric acid or air-particle abrasion). SBS test was performed using universal testing machine until failure, and failure modes were visually analyzed. Translucency parameter and curing-light transmission values through 1, 2, and 3 mm thickness were quantified using spectrophotometry and the MARC resin calibrator, respectively. Scanning electron microscopy (SEM) was used to examine the CAD/CAM composites after surface treatment. Composite type and surface treatment had a significant effect on SBS. Laboratory composite showed the highest SBS value (22.4 MPa). Cerasmart 270 exhibited higher translucency parameter values (19.8, 11.0, 5.0) than SFRC (14.5, 5.2, 1.6) at the three composite thicknesses tested. Air-particle abrasion was more effective in enhancing SBS than acid etching. Experimental SFRC CAD/CAM composite showed higher SBS values than Cerasmart 270. For all composites, translucency parameter values and light transmission decreased as thickness increased.